Uji Bioavailabilitas Tablet Floating Aspirin - Siswanto, Agus; Fudholi, Achmad; Nugroho, Akhmad Kharis; Martono, Sudibyo (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Aspirin is a non-steroidal anti-inflammatory drug with potential as antiplatelet for stroke prophylaxis. Several approaches of aspirin formulations in various dosage forms have been performed. Formulations of aspirin in conventional tablet dosage form often cause gastric irritation. Aspirin is rapidly absorbed in the upper gastrointestinal tract, especially the first small intestine. Therefore formulation of floating drug delivery system are designed to improve the bioavailability of aspirin. The floating system will retain the tablet in stomach, allowing sufficient absorption time for aspirin in stomach and upper intestine. Aim of this study was to determine relative bioavailability of aspirin floating tablets compared to the aspirin enteric coated tablets in rabbits with crossover design method. Serial blood samples were collected from rabbit ear marginal vein over a 10-h period. Drugs concentration in plasma (aspirin and salisylic acid) were determined by HPLC with benzoic acid as internal standard. The results showed that the floating aspirin tablet has better bioavailability with shorter tmax and more uniform of aspirin levels compared to enteric coated tablets, though the parameters AUC and Cpmax both of those products were not significant (p> 0.05).